2007
DOI: 10.1007/s11695-007-9371-0
|View full text |Cite
|
Sign up to set email alerts
|

Enterohormonal Changes After Digestive Adaptation: Five-Year Results of a Surgical Proposal to Treat Obesity and Associated Diseases

Abstract: Based on physiological and supported by evolutionary data, this procedure creates a proportionally reduced gastrointestinal (GI) tract that amplifies postprandial neuroendocrine responses. It leaves basic GI functions unharmed. It reduces production of ghrelin and resistin and takes more nutrients to be absorbed distally enhancing GLP-1 and PYY secretion. Diabetes was improved significantly without duodenal exclusion. The patients do not present symptoms nor need nutritional support or drug medication because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 35 publications
1
52
1
2
Order By: Relevance
“…Both DJB and jejunal resection normalized S I in diabetic rats as shown by S I levels equivalent to those of Wistar rats (S I = 1.01 6 0.06 3 10 24 min 21 $ pM 21 ; P = NS). Glucose effectiveness did not change after operations in any group.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Both DJB and jejunal resection normalized S I in diabetic rats as shown by S I levels equivalent to those of Wistar rats (S I = 1.01 6 0.06 3 10 24 min 21 $ pM 21 ; P = NS). Glucose effectiveness did not change after operations in any group.…”
mentioning
confidence: 76%
“…) and jejunectomy (S I = 0.80 6 0.14 3 10 24 min 21 $ pM 21 ), but not after ileectomy or sham operation/pair feeding in diabetic rats. Both DJB and jejunal resection normalized S I in diabetic rats as shown by S I levels equivalent to those of Wistar rats (S I = 1.01 6 0.06 3 10 24 min 21 $ pM 21 ; P = NS).…”
mentioning
confidence: 92%
“…33 Finally, a recent report of 228 subjects who had sleeve gastrectomy, omentectomy and initial jejunectomy demonstrated increases in PYY and GLP-1 levels postprandially in a subgroup of 17 subjects, which was accompanied by earlier satiety, no adverse effects and better quality of life 5 years after surgery. 34 There are discrepancies regarding the potential role of PYY as a satiety factor. Peripheral injections of PYY 3-36 into rats inhibited food intake and reduced weight gain, whereas an infusion into humans reduced appetite and food intake, 4 as well as decreased caloric intake in obese and lean subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Pardina et al (2012) showed that gastric bypass leads to normalisation of the hematological profile and a decrease in PAI-1 levels which in turn results in a decreased risk of thromboembolism in severely obese individuals. Bariatric surgery has also been shown to maintain raised levels of adiponectin, an anti-inflammatory agent (Nijhuis et al, 2007) and resistin which may contribute to a decrease in atherosclerotic events post surgery (Santoro et al, 2008). Hence bariatric surgery may be an effective way of managing obesity and cardiac failure with subsequent knock on effects on the metabolic syndrome, coronary heart disease, and type II diabetes (Ashrafian, le Roux, Darzi, & Athanasiou, 2008) compared to other weight loss therapies.…”
Section: Effects Of Weight Loss On Fibrinolysismentioning
confidence: 99%